A multiple hydrogen-bond scaffold based on dipyrimidin-2-ylamine - Sontjens, SHM; Meijer, JT; Kooijman, H; Spek, AL; van Genderen, MHP; Sijbesma, RP; Meijer, EW (Organic letters, 2001)
[GRAPHICS] A multiple hydrogen-bond array based on dipyrimidin-2-ylamine is presented, which is easily accessible. The influence of a preorganizing intramolecular hydrogen bond, tautomeric equilibria, and steric effects on the association behavior were investigated. X-ray diffraction shows that the molecules feature an ADA (acceptor-donor-acceptor) array of hydrogen-bonding sites in the solid state. The array persists in solution, and H-1 NMR titrations show that molecules with sterically nondemanding DAD arrays are selectively bound.